A ḍamaru for Jagat-Candra: a historical musical instrument from Nepal - Nutandhar Sharma; Richard Widdess (European Bulletin of Himalayan Research)
Historical musical instruments are rare in Nepal. So far, a few examples of ritual instruments associated with former rulers have been identified. A previously unpublished hour-glass-shaped pellet-drum (ḍamaru) from seventeenth-century Bhaktapur is of special interest because it bears inscriptions and representations of human figures that indicate the date and circumstances of its creation. Particularly significant are the name ‘Jagat-Candra’ – the joint pseudonym of King Jagatprakāśa Malla (ruled Bhaktapur 1643–1672) and his Chief Minister Candraśekhara Siṃha (d 1662) – and a combined portrait of this pair. In the article we describe the instrument, translate the inscriptions, identify all names and figures, consider the possible purpose of the drum’s creation, and assess the symbolic significance of the instrument with reference to the ritual purposes and religious associations of the ḍamaru in South Asia. The ḍamaru of Jagat-Candra demonstrates the close relationship in seventeenth-century Bhaktapur between sound, religious and royal authority, and the worship of Śiva and his consorts; it illustrates the richness of social and cultural significance that a historical musical instrument can carry.